Assessment of nursing undergraduate's perceptions of Interprofessional learning: A cross-sectional study - Bashatah, Adel S. (Frontiers in Public Health, 2023)
Background: Inter-Professional Learning (IPE) is based on mutual respect, and it improves collaboration and teamwork, and satisfaction among students and professionals. Objective This study aimed to assess the perceptions of IPE among Nursing students in Saudi Arabia. Methods: This is a cross-sectional survey-based study conducted among students from three different universities in Saudi Arabia, among nursing students over six months from May 2021-October 2021. Descriptive analysis was used to assess the perceptions of IPE and inferential testing was used to assess the association of perception scores among variables using a statistical package for social science version 26 (SPSS). Results: A total of 517 participants responded to the questionnaires. A higher proportion (n=281, 54.4%) of the participants were females, and were between 21-24 (n=350; 67.7%) years old. The mean age of the participants was 21.35 (SD=1.46). The majority of them were from King Saud University (n=273, 52.8%), followed by King Khalid University (n=127, 24.6%). Of the participants (80.4 %) agreed learning with other students will help them to become more effective members of a healthcare team. The mean overall score for RIPLS was 70.85(SD=6.611). The mean score for teamwork and collaboration was 37.19(SD= 4.79), professional identity, 23.23(SD=2.89), roles and responsibilities 10.42(SD=2.20). The mean score is significantly associated with the university type (p=0.0001), and previous knowledge of IPE (p=0.0001). Conclusion: The majority of the students had positive perceptions of understanding IPE and a good level of preparation for IPE. This means that if IPE is conducted among Saudi students, students will benefit from it, and it has the potential to improve their capacity to deliver holistic nursing care to their patients.